2016
DOI: 10.4103/1119-3077.188699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal/internal fit of chrome-cobalt crowns: Direct laser metal sintering versus computer-aided design and computer-aided manufacturing

Abstract: DMLS was best fitting fabrication techniques for single crown based on the results.The best fit was found in marginal; the larger gap was found in occlusal.All groups were within the clinically acceptable misfit range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
2
37
1
4
Order By: Relevance
“…(14,27) In this research, to minimize variations inherent to any manual process, the wax patterns for frameworks fabricated by the casting procedure were constructed by the CAD/CAM technology similar to other researches how found that Co-Cr frameworks obtained from milled wax patterns had better marginal and internal fit than those obtained from manually fabricated wax patterns. (7,10) Misfiting implant cemented restorations can lead to biomechanical failure, components fracture or even bone loss. (2,16) Studies evaluating the marginal adaptation of fixed restorations on teeth or implants suggest different methods of measuring marginal discrepancy between the restoration margins and abutment tooth or implant abutment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(14,27) In this research, to minimize variations inherent to any manual process, the wax patterns for frameworks fabricated by the casting procedure were constructed by the CAD/CAM technology similar to other researches how found that Co-Cr frameworks obtained from milled wax patterns had better marginal and internal fit than those obtained from manually fabricated wax patterns. (7,10) Misfiting implant cemented restorations can lead to biomechanical failure, components fracture or even bone loss. (2,16) Studies evaluating the marginal adaptation of fixed restorations on teeth or implants suggest different methods of measuring marginal discrepancy between the restoration margins and abutment tooth or implant abutment.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the direct microscopic, sectioning and replica methods were mostly preferred. (5,7,(10)(11)(12)(13)17,19,21) The direct microscopic method is easier, faster, and can be easily repeated, although the precision of the measurements is lower. Conversely, the sectioning method demonstrates the marginal discrepancy more clearly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations